Peculiarities of memory reproduction function in patients with exogeno-organic (cerebrotravmatic) pathology - V. Ye. Kazakov (Kazimierz Wielki University, 2017)
In order to establish the features of the reproductive function of memory in patients with pathology of exogenous-organic (cerebrotraumatic) genesis, 82 patients with a traumatic brain injury was examined. The patients was divided into two groups according to the severity of traumatic brain injury: the first group of the study included 30 patients with mild traumatic brain injury, the second group of the study included 32 patients with severe traumatic brain injury. As part of the study, anamnestic, clinical, neurological, psychopathological, psychodiagnostic, and follow-up studies was used. All patients underwent magnetic resonance imaging of the brain in dynamics. The psychodiagnostic study included the method of retained members of the series (G. Ebbingauz) with the presentation of verbal stimulus material and the analysis of the results three times: after the two submissions and 2 hours after the last submission. Patients were examined four times - after 3 months, after 6 months, after 1 year and after 3 years after traumatic brain injury. The study made it possible to establish the severity and dynamics of mnestic disorders depending on the time elapsed after traumatic brain injury and on the localization of damage to brain tissue. The maximum decrease in the reproductive function of memory was noted during the first three months after a traumatic brain injury; in the period between six months and the year after a traumatic brain injury, the reproductive function of memory was resumed, its indicators took the form of a plateau; in the future, outside this period, the violations of the mnestic disorders was resumed, negative dynamics was noted. The obtained data expands the idea of the features and dynamics of the reproductive function of memory in patients with pathology of exogenous-organic (cerebrotraumatic) genesis. This allows to improve the quality of the prognosis of the course of the disease and indicates the need to adjust therapeutic approaches in accordance with the established features of violations of the mnestic sphere in patients after traumatic brain injury.